MAKE A COMPOSITE FROM POLYETHYLENE TEREPHTHALATE (PET) PLASTIC WASTE BASED ON SEA PANDAN LEAVES (Pandanus tectorius) - Nuryati Nuryati; Raden Rizki Amalia; Nina Hairiyah (Jurnal Agroindustri, 2020)
Composite is a material that is formed from a combination of two or more forming materials through an inhomogeneous mixing consisting of two parts, namely the matrix as a composite binder or protector and the filler as a composite filler. Pandan sea leaf (Pandanus tectorius) is one alternative natural material that can be used as a filler in making composites because it has a high cellulose content and has strong fiber properties. The purpose of this research was to describe the process of making composites with natural fiber fillers and characteristics of composites produced. Making composites through 4 steps, namely making sea pandanus leaf powder, making cellulose fraction, making polyethylene terephthalate (PET) plastic waste matrix, and making composite. Based on the results of the composite characterization research includes water content from 2.46% to 3.51%, density from 0.49 g/cm3 to 0.52 g/cm3, porosity from 10.02% to 24.06%, and absorption water that is 24.88% to 46.51%. The type of MPA 1 (30% filler cellulose sea pandanus leaves: 70% polyethylene terephthalate pellet matrix) had a moisture content that complies with SNI 01-4449-2006 that is 2.46%, the corresponding density value SNI 03-2105-2006 is 0.52 g/cm3, the porosity value that is in line with SNI 03-2105-2006 is 10.02%, and the absorption according to JIS A5905-2003 standard is 24.88%.